Current progress of Pt-based ORR electrocatalysts for PEMFCs: An integrated view combining theory and experiment. (July 2021) - Cruz-Martínez, H.; Rojas-Chávez, H.; Matadamas-Ortiz, P.T.; Ortiz-Herrera, J.C.; López-Chávez, E.; Solorza-Feria, O.; Medina, D.I.
Abstract: The sluggish kinetics of oxygen reduction reaction (ORR) affects the massive use of polymer exchange membrane fuel cells (PEMFCs). Therefore, the use of electrocatalysts is required to accelerate the ORR kinetics. Usually, Pt/C electrocatalysts are used for the ORR. Nevertheless, the principal disadvantages of using Pt are its high-cost, low availability, and limited stability. For these reasons, research of more stable and cost effective electrocatalysts with high electrocatalytic activity is important to achieve large-scale power generation. To date, there are significant advances and great opportunities for the design of novel electrocatalysts with high electrocatalytic activity and stability for the ORR through the connection of experimental and theoretical explorations. For these reasons, in this review, combined theoretical–experimental studies for the design of novel Pt-based metallic electrocatalysts for the ORR are revised and analyzed in detail. Graphical abstract: Image 1 Highlights: Theoretical predictors and experimental parameters used for the comparison of ORR electrocatalytic activity are revised. The combined theoretical-experimental studies for the design of novel Pt-based metal electrocatalysts for the ORR are revised and analyzed. There are significant advances for the design of novel electrocatalysts toward the ORR combining theory and experiment. Numerous combined theoretical-experimental studies of Pt-based bimetallic electrocatalysts for the ORR have been developed. Few theoretical and experimental studies analyze the activity and stability of Pt-based bimetallic electrocatalysts supported on novel support materials.